Mapping the Research Landscape on Poaching: A Decadal Systematic Review - Lavadinović, Vukan M.; Islas, Camila A.; Chatakonda, Murali Krishna; Marković, Nevena; Mbiba, Monicah (Frontiers in Ecology and Evolution, 2021)
Poaching is a widespread activity which affects wildlife management goals and undermines conservation efforts worldwide. Despite its complexity, poaching is still commonly addressed by researchers as a one-dimensional phenomenon. In order to deepen the scientific understanding of poaching, we conducted a systematic literature review in the Web of Science and Scopus databases for the last ten years, following the PRISMA methodology. We found that most studies were carried out in Africa, although 43% of all articles on poaching were published by researchers from the United States and the United Kingdom. Most studied species are elephants (22%), rhinos (19%), wolves (9%) and bears (6%). Even though this study identified a wide range of motives and drivers behind poaching activities, more than half of the analyzed papers do not attempt to provide a deeper understanding of this phenomenon. Its understanding of poaching usually does not go beyond the environmental impact of illegal hunting. Potential limitations of our study may relate to the focus on exclusively English-language articles and, among them, only those discussing mammal, bird and reptile species. Our findings indicate that global scientific knowledge on poaching in the last ten years is biased. There is an imbalance between the developed countries which mostly produce knowledge on poaching (usually from Northern America and Europe), and the developing countries which are commonly an object of interest. This bias is potentially challenging, since the global scientific knowledge on poaching comes from limited experience based on charismatic species and selective case studies. To overcome this gap and develop a deeper understanding of poaching, the scientific community needs to overcome this bias and address illegal hunting wherever it affects the environment and undermine conservation efforts.